Control of weeds in imidazolinone tolerant maize with imazethapyr plus imazapyr - James, T.K.; Rahman, A.; Gray, J. (New Zealand Plant Protection, 2001)
Three trials conducted in Waikato evaluated the use of the proprietary imidazolinone herbicide mixture of imazethapyr plus imazapyr for weed control in imidazolinone tolerant (IT) maize crops A range of herbicide rates application times and adjuvants were evaluated The results show that imazethapyr/imazapyr herbicide mixture was very effective in controlling a variety of both monocotyledonous and dicotyledonous annual weeds Some perennial weeds present in the trials were also well controlled Imazethapyr/imazapyr was more effective when applied early postemergence and Hasten was the most effective adjuvant for increasing the efficacy of imazethapyr/imazapyr The IT maize crop and final grain yields were not affected by these herbicides